2012
DOI: 10.1186/1476-511x-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Rice protein improves adiposity, body weight and reduces lipids level in rats through modification of triglyceride metabolism

Abstract: BackgroundTo elucidate whether rice protein can possess a vital function in improving lipids level and adiposity, the effects of rice proteins extracted by alkaline (RP-A) and α-amylase (RP-E) on triglyceride metabolism were investigated in 7-week-old male Wistar rats fed cholesterol-enriched diets for 2 weeks, as compared with casein (CAS).ResultsCompared with CAS, plasma concentrations of glucose and lipids were significantly reduced by RP-feeding (P < 0.05), as well as hepatic accumulation of lipids (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In our study, high rice consumption was strongly correlated with a healthy low-wheat diet pattern (low wheat, high fish and seafood intake) in the Central region. Another possible reason could be the up-regulation of lipolysis and the down-regulation of lipogenesis by rice protein, which has been reported in a study in rats that showed improved adiposity and body weight after rice protein feeding[36]. In addition, fried rice is commonly consumed in China by cooling steamed rice in the refrigerator overnight and stir-frying it with oil; recent studies have shown that these processes promote rice starch retrogradation, increase the resistant starch concentration of rice and reduce the rice calories[37].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, high rice consumption was strongly correlated with a healthy low-wheat diet pattern (low wheat, high fish and seafood intake) in the Central region. Another possible reason could be the up-regulation of lipolysis and the down-regulation of lipogenesis by rice protein, which has been reported in a study in rats that showed improved adiposity and body weight after rice protein feeding[36]. In addition, fried rice is commonly consumed in China by cooling steamed rice in the refrigerator overnight and stir-frying it with oil; recent studies have shown that these processes promote rice starch retrogradation, increase the resistant starch concentration of rice and reduce the rice calories[37].…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment was performed in compliance with the Guidelines of the Committee for Animal Experimentation of Harbin Medical University and followed the same protocol used in previous studies (Yang et al, 2011a(Yang et al, , 2012b. Seven-week-old male Wistar rats were purchased from the Animal Center of Harbin Medical University (Harbin, China) and individually housed in metabolic cages in a room maintained at 22 ± 2°C under a 12 h light-dark cycle (07:00-19:00 light).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Longjing 26 (Rice Research Institute of Heilongjiang Academy of Agricultural Sciences, Jiamusi, China) and casein (CAS) (Gansu Hualing Industrial Group, Gansu, China) were used as the dietary protein sources in the present study. RP was prepared by the alkaline extraction method (Yang et al, 2011a(Yang et al, , 2012b.…”
Section: Protein Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Furthermore, the ability of the rice protein to control body weight gain and plasma cholesterol levels is well established, perhaps due to the relatively low digestibility of rice protein. 34,35 For the HF-CR diet, we replaced the corn starch and sucrose present in the HF with cooked rice powder, which had 34 g of rice protein per kg total food weight. This may be helpful for decreasing body weight gain and fat accumulation.…”
Section: Cooked Rice Inhibits Hepatic Fat Accumulation 39mentioning
confidence: 99%